ta có
[(x+6)(x+7)+(4+x)(x+7)]+(x+4)(x+5)
=[(x+7)(x+6+x+4)]+(x+4)(X+5)
=(x+7)(2x+10)+(x+4)(x+5)
=(x+7)2(x+5)+(x+4)(x+5)
=(x+5)(2x+14+x+4)
=(x+5)(3x+18)
(x+6).(x+7)+(x+4).(x+7)+(x+4).(x+5)
= x^2+13x+42+x^2+11x+28+x^2+9x+20
= 3x^2+33x+90
= 3.(x^2+11x+30)
=3.[(x^2+5x)+(6x+30)]
= 3.(x+5).(x+6)
Tk mk nha
(x + 6)(x + 7) + (x + 4)(x + 7) + (x + 4)(x + 5)
= (x + 7)(x + 6 + x + 4) + (x + 4)(x + 5)
= (x + 7)(2x + 10) + (x + 4)(x + 5)
= 2(x + 7)(x + 5) + (x + 4)(x + 5)
= 2(x + 5)(x + 7 + x + 4)
= 2(x + 5)(2x + 11)